Nontuberculous Mycobacterial Pneumonia Caused by Mycobacterium immunogenum: A Case Report and Literature Review - Huang S; Shangguan Y; Guo W; Ji Z; Jin X; Zhao R; Zheng L; Wang Y; Jiang L; Xu K (Infection and Drug Resistance)
Shujuan Huang,1,* Yanwan Shangguan,2,* Wanru Guo,1 Zhongkang Ji,1 Xiuyuan Jin,1 Ruihong Zhao,1 Lin Zheng,1 Yuping Wang,1 Liangxiu Jiang,1 Kaijin Xu1 1State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2Infection Control Department, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kaijin Xu, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, Zhejiang University, Hangzhou, People’s Republic of China, Tel +86-0571-87236440, Email zdyxyxkj@zju.edu.cnBackground: Mycobacterium immunogenum is a rare nontuberculous mycobacterium belonging to the Mycobacterium chelonae-abscessus group. Most cases reported in the past decade have been extrapulmonary infections, and reports of nontuberculous mycobacterial pulmonary disease (NTM-PD) caused by M. immunogenum are rare. Herein, we report a case of NTM-PD caused by M. immunogenum.Case Presentation: An 81-year-old man with a history of chronic kidney disease and cardiovascular disease was hospitalised in 2021 owing to pneumonia. Two sputum cultures tested positive for Mycobacterium. The mycobacterium biochip test identified M. abscessus and Mycobacterium gilvum, and whole-genome sequencing confirmed the identity as M. immunogenum. Antimicrobial drug susceptibility testing showed that the isolate was resistant to imipenem, moxifloxacin, and doxycycline; intermediately sensitive to tobramycin and linezolid; and sensitive to amikacin, cefoxitin, and clarithromycin. The patient was treated with cefoperazone sodium and sulbactam sodium (2 g twice daily) and switched to meropenem (0.5 g every 6 hours) for anti-infection but died due to acute respiratory failure and severe pneumonia before targeted treatment for NTM-PD could be initiated.Conclusion: NTM-PD is frequently diagnosed at an advanced stage, primarily because its clinical presentation is often atypical and definitive laboratory tests are not readily available. Therefore, greater attention should be paid to the diagnosis and treatment of NTM-PD. Nontuberculous mycobacterial infections, especially clinically rare infections, need to be diagnosed without delay and their antibiotic susceptibility needs to be determined.Keywords: nontuberculous mycobacterial pulmonary disease, whole-genome sequencing, antimicrobial susceptibility testing, treatment